2015
DOI: 10.1111/efp.12240
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between callus cultures of Pinus sylvestris and pine fungi with different trophic properties

Abstract: Fungal virulence may be studied using tissues cultures of host plants in dual cultures in vitro, enabling analyses of interactions with undifferentiated cells of their host plants. Three genotypes of Pinus sylvestris callus, initiated by somatic embryogenesis, were used for establishing dual cultures with fungi pathogenic, endophytic or saprotrophic on pine needles or shoots. Fungal growth towards the plant callus tissue differed, depending on the life strategy of the fungus. The pathogen Gremmeniella abietina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Chong et al 42 suggested that damages in cell membranes during the first days after elicitation of Morinda elliptica cell cultures with MeJA would trigger the biosynthesis of antioxidant enzymes, therefore inducing a subsequent decrease in MDA. Experiments using dual cultures have shown that the stimulation or inhibition of mycelium growth in these conditions could give useful information about plant susceptibility [43][44][45] , and therefore could be used to select efficient elicitation treatments 36,42 . In our study, elicited holm oak somatic embryos did not inhibit Phytophthora cinnamomi mycelium growth in dual culture tests, being the plates with somatic embryos elicited with PFE-50, 50 µM BTH, 5, 10 or 50 µM MeJA and 5 µM PABA those showing ratios higher than 1 between growth towards control and growth towards elicited material at the end of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Chong et al 42 suggested that damages in cell membranes during the first days after elicitation of Morinda elliptica cell cultures with MeJA would trigger the biosynthesis of antioxidant enzymes, therefore inducing a subsequent decrease in MDA. Experiments using dual cultures have shown that the stimulation or inhibition of mycelium growth in these conditions could give useful information about plant susceptibility [43][44][45] , and therefore could be used to select efficient elicitation treatments 36,42 . In our study, elicited holm oak somatic embryos did not inhibit Phytophthora cinnamomi mycelium growth in dual culture tests, being the plates with somatic embryos elicited with PFE-50, 50 µM BTH, 5, 10 or 50 µM MeJA and 5 µM PABA those showing ratios higher than 1 between growth towards control and growth towards elicited material at the end of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…When host plants are used as vectors for transcriptome level research, a small number of expressed endophyte genes are typically disregarded due to the significant background of plant genes (Porras-Alfaro and Bayman, 2011 ). The callus is an undifferentiated living cell structure of plants that contains a set of defense systems similar to host plants (Nawrot-Chorabik et al, 2016 ). In this study, we used dual cultures of rice callus and P. liquidambari to simulate an endophytic environment in which organisms can release signals to recognize each other and form a relationship of simulated antagonism balance.…”
Section: Discussionmentioning
confidence: 99%
“…The endophytic lifestyle was studied using tissues cultures of host rice in dual culture in vitro based on previous research (Sieber et al, 1990 ; Peters and Schulz, 1998 ; Nawrot-Chorabik et al, 2016 ). Inoculated rice seeds at the surface were sterilized in callus solid medium (1 × NB solid medium, 2 mg L −1 2,4-D, 30 g L −1 sucrose, 10 g L −1 agar, pH 7) and cultivated for 20 days at 28°C.…”
Section: Methodsmentioning
confidence: 99%
“…The documented responses involving secondary compound production during the SE process suggest that interactions of SE-plants with biotic stresses could be affected. For instance, studies of host-pathogen interactions in early tissue development have shown that fungal mycelial growth is strongly reduced by inhibitory substances released by somatic embryos when grown together in culture ( Terho et al, 2000 ; Vookova et al, 2006 ; Hrib et al, 2013 ; Nawrot-Chorabik et al, 2016 ). Furthermore, changes in secondary compounds early in development may be persistent, as shown by plants propagated by SE to obtain compounds of medicinal interest.…”
Section: Introductionmentioning
confidence: 99%